Human Relationships in Higher Education: The Power of Collaboration, Creativity and Openness. Issue 1 (13th December 2021) - Nerantzi, Chrissi; Chatzidamianos, Gerasimos; Stathopoulou, Haroula; Karaouza, Efthymia
We educators may have been obsessed with perfection, expertise, polished experiences and performances too much for too long. Where is the human? Ironed out? This provocative opinion paper is a collection of the authors' reflections based on experiences, observations, ideas and readings. We invite educators to consider and explore what may help them (re-) connect with their inner selves and others socially, emotionally and cognitively in the context of learning and teaching in HE during the COVID-19 pandemic and beyond. With reference to a collaborative creative initiative that was implemented under the auspices of the Global OER Graduate Network, the paper aims to instigate a discussion around the importance of building and sustaining effective relationships in HE. These are perceived as the drivers that potentially boost participation and student success using collaboration, creativity and openness. Working in partnership with students, recognising and accepting individuality as well as creating opportunities for connection can support the operationalisation of these reflections in practice.